Development and characterization of hybrid liquid fertilizer from celery and cucumber wastes - Shamsul, Zakaria; Mohammad Sufian, Zahari; Siti Zulaikha, Hisamudin (Elsevier Ltd, 2022)
Agriculture is one of the most important sectors in Malaysia. Since huge amount of vegetable wastes gives negative impacts towards the environment, they can be used to produce hybrid liquid fertilizer to facilitate the growth of the plant. Hybrid liquid fertilizer is a fertilizer that is made from addition of ammonia to fermented liquid from the fermentation of vegetable wastes and brown sugar. The objectives of this study are to produce hybrid liquid fertilizer as a growth booster from fermentation, to characterize the developed hybrid liquid fertilizer, and to analyze the effect of hybrid liquid fertilizer on the growth of mung beans. The hybrid liquid fertilizer obtained was used to analyze the nutrients content by using ICP-MS. pH of the hybrid liquid fertilizers were also tested. The result showed that the pH decreases as days of fermentation increases due to the production of acids. In ICP-MS analysis, potassium content in the samples increases with increasing days of fermentation. The same trend goes for phosphorous except for the hybrid liquid fertilizer of cucumber with 4 g of ammonia. Hybrid liquid fertilizer of celery with 2 g of ammonia at 7 days fermentation showed to be the most suitable to be used for the growth of plant as it produced the best results for the height of mung bean plant, the length of the leaves and the width of the leaves.